COMPARATIVE EFFICIENCY ESTIMATION OF PSYCHOMETRIC SCALES IN PATIENTS WITH ISCHEMIC HEART DISEASE AND ARTERIAL HYPERTENSION - Kulik, A.L.; Serikova, O.I.; Yabluchanskiy, N.I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Based on results of 62 patients’ checkup with the pain form of ischemic heart disease and arterial hypertension the correlation analysis between the indexes of psychical and clinical status was taken. Maximum correlation level with basic clinical parameters was determined by using the Hamilton depression scale and Hospital anxiety and depression scale that allows to recommend exactly these scales for patients’ psychoemotional status estimation.